Andragogy Principles In Arabic Learning At Diniyyah Putri Lampung - Kemas Faisal Al-Azam (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
This study aims to describe the Andragogy Principles In Arabic Learning at MTs Diniyyah Putri Lampung. This research uses a qualitative approach with a case study method. This method is used because the researcher wants to explore carefully and in-depth the work or activities of individuals or all individuals at MTs Diniyyah Putri Lampung. With this approach, researchers will obtain in-depth data or information related to the purpose of this study. From the data analysis that the author did, it was concluded that there are Andragogy Principles in most of the Arabic language learning activities at MTs Diniyyah Putri Lampung. This can be seen in several aspects of learning, for example, the provision of motivation in the introduction to learning that contains useful values, the practice of providing the material that provides experience, and the material is also related to daily problems, in assignments, there are practices assigned by the teacher. . The learning process is as needed, and interesting. Students participate actively, cooperate, so as to make the learning process not rigid and the teacher uses varied learning methods that eliminate the fear factor in Arabic subjects. besides that, there is also a process of Directing and motivating but not telling (guiding and asking; not telling), and teachers and students showing enthusiasm in learning Arabic